KEWARGANEGARAAN YANG BERBASIS PANCASILA: MEMBANGUN RASA CINTA TANAH AIR DI KALANGAN GENERASI MUDA DESA HILISATARO - Darwin Gaurifa (Universitas Nias Raya, 2023)
This community service aims to instill a sense of patriotism among the youth of Hilisataro Village through a Pancasila-based understanding of citizenship. To achieve this, we conducted a series of educational and interactive activities, including discussions, seminars, and cultural events. This approach aims to enhance the awareness of young people regarding the importance of Pancasila values as the foundation of nationhood and statehood. The results of these activities indicate an improvement in participants' knowledge and understanding of citizenship, as well as a strengthened and lasting sense of patriotism. It is hoped that this initiative will create a generation of youth who are more concerned about their environment and local culture.